Usos y prácticas de la medicina tradicional para el tratamiento del Covid 19 en la comunidad de Miraflores río tigre, distrito de Nauta 2022 - Rengifo Meléndez, Roldán (2023)
The present investigation, entitled "Uses and practices of traditional medicine for the treatment of COVID-19 in the Miraflores community, Tigre river, Nauta District, 2022", was developed in the Nauta district, Loreto province, Loreto region. Its main objective is to describe the use of the biodiversity of plant and animal species in the practice of traditional medicine for the treatment of COVID-19. The methodology used in the research has a qualitative approach, of a descriptive type and ethnographic design. The data collection techniques and instruments in the field were the following: participant observation and semi-structured interviews. The results of the research show that traditional medicine was a widely used practice in the community and very helpful in the treatment of COVID-19, when the pandemic reached the community in 2020. In the Miraflores native community, interviews were 17 key community members who used traditional medicine made up of 21 medicinal plants, mainly using the leaves and the bulb; and to a lesser extent the stem and bark. Pills were also purchased at the community health post. Traditional medicine is considered a very important resource in the treatment of diseases in the Miraflores native community.